Penerapan Nilai -Nilai Karakter melalui Budaya Sekolah di MI Ar Rahmah Jabung - Malang - Muhammad Khoirul Anam Ma'ruf; Isroqunnajah Isroqunnajah; Ahmad Nurul Kawakip (Journal on Education, 2023)
This research focuses on three things, namely: (1) school culture applied at MI Ar Rahmah Jabung, (2) Implementation of character values ​​through school culture at MI Ar Rahmah Jabung, (3) obstacles encountered in applying the values character values ​​through school culture at MI Ar Rahmah Jabung.The research that has been carried out uses a qualitative descriptive approach using several data collection processes between observation, interviews and documentation. From the research conducted, the research results were obtained to answer the existing research focus, namely: (1) There are several school cultures that are applied at MI Ar Rahmah Jabung, including h: Culture of Prayer, Koran, Discipline, Reading. (2) MI AR Rahmah carries out the application of character values ​​to students which are carried out at school, where the activities are divided into 3 namely routine, programmed, and spontaneous activities. In implementing the culture of praying, reciting the Koran, discipline and reading, it has been programmed and starts from the planning, the activity process, to the evaluation, (3) In implementing character values ​​through the school culture at MI Ar Rahmah Jabung, there are obstacles including: Lack of awareness from some residents school, the percentage of the number of teachers is not proportional to the number of students, not the Counseling teacher, the social environment of the students is diverse, students do good only in front of the teacher, lack of attention from parents, the nature of students who are still unstable.